(untitled) (International journal of artificial intelligence, 2025)
This article examines the lexico–semantic features of the formation of medical terminology in modern English. The study focuses on the structural, morphological, and semantic processes that shape the vocabulary of medicine, including borrowing, compounding, affixation, and semantic extension. The analysis reveals that medical terms are formed not only through linguistic mechanisms but also through cognitive and cultural factors reflecting the evolution of medical science. The study emphasizes the importance of understanding these processes for translators, linguists, and medical professionals, as precise terminology contributes to clarity and accuracy in professional communication.